Substance P potentiates thermal hyperalgesia induced by intrathecal administration of D-serine in rats - Zhang Yi-Hong; Shu You-Sheng; Zhao Zhi-Qi (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the functional interaction between substance P (SP) and D-serine, agonist for glycine regulatory site of N-methyl-D-aspartate (NMDA) receptor, in processing spinal nociception. Methods: Behavior studies, by testing tail-flick latency (TFL) combined with intrathecal application of drugs, were conducted in lightly anesthetized rats. Results: Decrease in TFL was observed 1.5 min after intrathecal injection of D-serine 1000 nmol. Following pretreatment with SP 0.05 nmol 6 min prior to injection of D-serine 10 nmol, D-serine-induced decrease in TFL was greatly enhanced. The potentiation was blocked by co-administration of 7-chlorokynurenic acid 1 pmol, the selective antagonist for glycine regulatory site of NMDA receptor, or H-7 10 micromol, the PKC non-selective inhibitor, with SP 0.05 nmol. Conclusion: SP potentiates the D-serine-induced thermal hyperalgesia. Glycine regulatory site of NMDA receptor and intracellular protein kinase system may participate in the interaction of SP and NMDA receptor in the spinal cord.